Social Changes in Israeli Society and Their Impact on the Importance of Work Outcomes. (March 2015) - Sharabi, Moshe
Over the last 30 years, Israeli society has undergone dramatic social, political and economic changes, and this study examines changes in the importance of the valued work outcomes between 1981 and 2006. Results are reported for cross-sectional studies conducted in 1981 ( n = 973) and 2006 ( n = 909), which were drawn from representative samples of the Israeli workforce. The samples allow us to examine the cohort effect/generational differences and the ageing effect. The findings reveal substantial differences in work outcome importance over the course of time. Between 1981 and 2006, there was a decrease in the importance of the intrinsic outcome of interest and the social outcome of serving society while the importance of the extrinsic outcomes of income, status and prestige increased. This trend reflects the transformation from a collectivist and altruistic society to an individualist and materialistic society, and can be explained by the generational/cohort effect and ageing effect. The changes in work outcomes over the course of time are explained by political, social and economic factors.